2021
DOI: 10.1007/s12207-021-09406-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparability and Validity of the Online and In-Person Administrations of the Inventory of Problems-29

Abstract: While the psychometric equivalence of computerized versus paper-and-pencil administration formats has been documented for some tests, so far very few studies have focused on the comparability and validity of test scores obtained via in-person versus remote administrations, and none of them have researched a symptom validity test (SVT). To contribute to fill this gap in the literature, we investigated the scores of the Inventory of Problems-29 (IOP-29) generated by various administration formats. More specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Indeed, it showed superior validity in the discrimination between genuine and experimentally feigned depression, PTSD and schizophrenia over the widely utilized SIMS (Giromini, et al, 2018), and it was shown to provide incremental validity when used with the TOMM Viglione et al, 2017) or Minnesota Multiphasic Personality Inventory-2 (MMPI-2; . Furthermore, it demonstrated similar sensitivity to various symptom presentations, including depression, PTSD, mTBI and schizophrenia-related diagnoses , and its validity has been demonstrated in various formats and cultural contexts (e.g., Banovic et al, 2021;Carvalho et al, 2021;Gegner et al, 2021;Giromini et al, 2021;Ilgunaite et al, 2020;Roma et al, 2019;Šömen et al, 2021;Winters et al, 2020).…”
Section: The Inventory Of Problems-29 (Iop-29; Viglione and Giromini ...mentioning
confidence: 92%
“…Indeed, it showed superior validity in the discrimination between genuine and experimentally feigned depression, PTSD and schizophrenia over the widely utilized SIMS (Giromini, et al, 2018), and it was shown to provide incremental validity when used with the TOMM Viglione et al, 2017) or Minnesota Multiphasic Personality Inventory-2 (MMPI-2; . Furthermore, it demonstrated similar sensitivity to various symptom presentations, including depression, PTSD, mTBI and schizophrenia-related diagnoses , and its validity has been demonstrated in various formats and cultural contexts (e.g., Banovic et al, 2021;Carvalho et al, 2021;Gegner et al, 2021;Giromini et al, 2021;Ilgunaite et al, 2020;Roma et al, 2019;Šömen et al, 2021;Winters et al, 2020).…”
Section: The Inventory Of Problems-29 (Iop-29; Viglione and Giromini ...mentioning
confidence: 92%
“…Moreover, we administered the paper-and-pencil version of the PAI in both samples; in contrast, we administered the paper-and-pencil version of the IOP-29 in prison, whereas we used both the in-person, paper-and-pencil and computerized versions of the IOP-29 in the community sample. It should be noted, however, that the administration format is known to have no influence on IOP-29 testing results (Giromini et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…A second emerging research area in Italy concerns the investigation of the effectiveness of several SVTs and PVTs. In particular, numerous recent studies examined the psychometric properties of the Italian IOP-29, reporting on its concurrent (Giromini et al, 2018), incremental (Giromini et al, 2019), and ecological (Roma et al, 2020) validity, on its applicability to multiple symptom presentations (Giromini et al, 2020), and on the equivalence of its online and paper-and-pencil formats (Giromini et al, 2021). Additionally, some authors also investigated the effectiveness of the SIMS and MMPI-2 in detecting noncredible presentations (e.g., Mazza et al, 2019), and a recently published article described the development and initial validation of the IOP-M, a new, add-on, PVT module designed to be used in combination with the IOP-29 (see also Banovic et al, 2021;Carvalho et al, 2021;Gegner et al, 2021).…”
Section: Italymentioning
confidence: 99%
“…Also, before psychologists can use a test remotely, the copyright holder of the instrument must agree to their test being used in this manner. To our knowledge, only one European study has addressed the question of paper-pencil versus online presentation to date (Giromini et al, 2021). It is, therefore, necessary to conduct more systematic research into these problems.…”
Section: Major Challenges For Future Developmentsmentioning
confidence: 99%